2009
DOI: 10.1111/j.1365-2672.2008.03974.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison ofVibriospp. populations found in seawater, in exhibition aquaria, in fish intestine and in fish feed

Abstract: Aims:  Vibrio populations in the seawater supply and the water of seven exhibition aquaria that simulate various Mediterranean and tropical ecosystems were compared. The similarity of Vibrio populations in the intestine of various fish species, feed and water was examined. Resistance to the antibiotics used in fish health management was analysed for the dominant Vibrio isolates. Methods and Results:  Samples were collected for 1 year from seven exhibition tanks reproducing different ecosystems. The diversity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…To date, Vibrio was mainly isolated from turbot skin, larval turbot gut and turbot‐associated seawater (Montes et al ., , ; Cerdà‐Cuéllar & Blanch, ). Many surveys also demonstrated that Vibrio was dominant in marine fish gut (Blanch et al ., ; Smriga et al ., ). In this study, this genus was observed in all parts of turbot GI tract, especially in rectum content (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…To date, Vibrio was mainly isolated from turbot skin, larval turbot gut and turbot‐associated seawater (Montes et al ., , ; Cerdà‐Cuéllar & Blanch, ). Many surveys also demonstrated that Vibrio was dominant in marine fish gut (Blanch et al ., ; Smriga et al ., ). In this study, this genus was observed in all parts of turbot GI tract, especially in rectum content (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…To date, most knowledge in relation to the normal GI microbiome of fish was based on the use of culture‐dependent and 16S rRNA gene‐based methods. The bacterial community of freshwater or marine fish GI tract seemed to be dominated by Proteobacteria and Firmicutes (Blanch et al ., ; Smriga et al ., ). Several special groups, such as probiotics, pathogens and cellulose‐decomposing bacteria, were also isolated from various freshwater or marine fish species (Vine et al ., ; Lazado et al ., ; Pérez‐Sánchez et al ., ; Wu et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Vibrio has been previously shown to occur at high abundance in fish (Austin & Austin ; Blanch et al . ; Sullam et al . ; Xing et al .…”
Section: Discussionmentioning
confidence: 99%
“…The ability of Vibrio representatives to resist low pH and bile supports their survival within the fish gut (Yoshimizu and Kimura, 1976). Whether food or water intake is the greater source of inoculation is an open question: some studies have found a strong effect of food source on gut Vibrio composition (e.g., Grisez et al, 1997), whereas others found a stronger influence of Vibrio representation in the water column (e.g., Blanch et al, 2009). Conversely, Vibrio content of the fish gut has also been shown to be responsible for increasing Vibrio abundance in surrounding water when fish were introduced into a tank that did not otherwise support Vibrio growth, demonstrating significant excretion of viable cells from the fish gut (Sugita et al, 1985).…”
Section: Biological Niches For Vibriomentioning
confidence: 99%